KONSELING KELOMPOK REALITA UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR SISWA MADRASAH IBTIDAIYAH, EFEKTIFKAH? - Faralia Nadhifa; Bakhrudin All Habsy; Tadoer Ridjal (Perspektif Ilmu Pendidikan, 2020)
is study aims to determine the effectiveness of reality group counseling in increasing pupils’ discipline in an islamic primary school. This study used an experimental design with a pretest and posttest control group design. The study was conducted for 6 months using a reality group counseling approach with metaphorical techniques and quality discussion. Data were analyzed using t-test. Based on the results of the study it was found that reality group counseling was effective to improve pupils’ learning discipline in the islamic primary school which was used as the research sample. Suggestions and recommendations from the results of this study include: 1) Guidance and Counseling teachers can apply the ralita group counseling service as an alternative to improving pupils’ discipline, 2) The next researcher can use other relevant techniques to test the effectiveness of reality group counseling.